SCHOOL PRINCIPLE LEADERSHIP IN DEVELOPING CHARACTER EDUCATION - Wasilah, Nur; Susilawati, Samsul; Hambali, Muh (Managere: Indonesian Journal of Educational Management, 2022)
The purpose of this study was to determine the principal's leadership in developing character education at SMPN 1 Galis Pamekasan. The research approach used in this research is qualitative research. This type of data analysis uses interview and observation methods. The results of the study show that the principal at SMPN 1 Galis Pamekasan develops character education by planning by making a good school vision, mission and goals that can foster good character for implementation and evaluation students. Implementation in developing the characteristics of mental and moral education.